Overseas air medical repatriation of national soccer players infected with COVID-19 and contacted staffs from Austria to South Korea - Choi, H. J.; Kim, H. J.; Seo, G. (Air Medical Journal, 2021)
Korea rarely has a system to transport patients from abroad. However, single patient transfer was steadily being carried out, and there was an experience of transferring a large number of personnel regardless of whether they were confirmed or not due to COVID-19. Recently, a national soccer game was held abroad, and a total of eight players and staff were infected. A total of 15 people, including these, were transported through a charter fully equipped with quarantine equipment by medical response team with experience in air transport.